Efecto de un recubrimiento comestible a base de proteína concentrada de lactosuero y cera de carnauba para la conservación de la claudia (Pronus domestica). - Naucin Azogue, Johanna Sara (2022)
This research aimed to preserve the fruit through the application of a coating based on concentrated whey protein and carnauba wax since there is a significant loss and waste in the post-harvest phase of climacteric fruits such as claudia (Pronus domestica), for which a Completely Randomized Block Design (DBCA) was used in a factorial arrangement of (2*2*2) + 2, subjected to twelve days. The coating was prepared in concentrations of 5 and 10% concentrated whey protein, 0.2 and 0.4% carnauba wax, applying eight treatments at room temperature and refrigeration, taking as reference two witnesses without coating (ambient and refrigeration) in which the physicochemical parameters were evaluated on days zero, one, three, six, nine and twelve; starting from an initial pH of 4.2, soluble solids 8.9 °Brix, titratable acidity 2.0%, firmness 4.33 N and weight 37.47g; identifying as the best treatment the t6 that it contains (concentrated whey protein 5 %, carnauba wax 0.4% at room temperature) at twelve days with pH 4.4%, soluble solids 10.00 °Brix, titratable acidity 2.4%, firmness 3.00 N and weight 28 .17g. In the microbiological analysis, the results are 25 CFU/g, total aerobes, 60 and <10 CFU/g of molds and yeasts, showing to be a stable treatment at 12 days since it did not present any deterioration in the fruit. On the other hand, the parameters with greater acceptability by the tasters in the sensory analysis were; color, neither light nor dark, delightful smell, very pleasant taste, and texture, neither hard nor soft from the best treatment. It was observed that the coating helps to preserve claudia without affecting their physicochemical and organoleptic properties, being an excellent alternative for the producer to avoid economic losses.